Oncogenic risk of hormone replacement in climacteric - Cervantes Begazo, René (2015)
Bittner in 1947 first proposed the concept that hormones may increase the incidence of neoplasia, based on his studies of estrogen and breast cancer in mice. After several studies the hypothesis of association between breast and endometrial cancer and estrogen administration arises, and breast cancer and progestogen administration. The hypotheses are based on "excessive association between neoplasia and hormonal stimulation of specific target organs, whose normal growth and function are controlled by one or more steroid or polypeptide hormones."